Unhealthy Food and Beverage Consumption and The Menstrual Cycle Among Female Adolescents - Shelpi Anggraeni; Emi Lindayani; Ida Nurhidayah (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
Menstrual cycle disorders are among the most common reproductive health issues experienced by adolescent girls and may affect future fertility. One factor influencing menstrual cycle regularity is the consumption of unhealthy foods and beverages, including foods high in fat, sugar, and salt, and sugary, carbonated, and caffeinated drinks. These dietary habits can disrupt hormonal balance through metabolic and endocrine mechanisms. This study aimed to determine the relationship between unhealthy food and beverage consumption and the menstrual cycle among female adolescents at SMAN Tanjungsari. A quantitative approach with a cross-sectional design was used. The sample consisted of 272 respondents selected through proportional random sampling. Research instruments included a Food Frequency Questionnaire (FFQ) and a menstrual cycle questionnaire. Data were analyzed using univariate and bivariate techniques with the Spearman Rho test. The results showed significant relationship between unhealthy food consumption and the menstrual cycle (p < 0.001), with strong positive rho value of 0.715. In addition, significant relationship was found between unhealthy beverage consumption and the menstrual cycle (p < 0.001), with a moderate positive rho value of 0.612. Therefore, the higher the frequency of consuming unhealthy foods and beverages, the greater the likelihood adolescents will experience menstrual cycle disorders.